Indeks Penulis Volume 36, Tahun 2016 - Indeks Penulis Volume 36, Tahun 2016 (agriTECH, 2016)
Agustiningrum, D.A. 369Aini, N. 160Amri, M.N. 226Anandito, R.B.K. 23Andarwulan, N. 117Andini, S. 261Anggrahini, S. 48Anisum 64Aprilia, S. 416Apriyanto, M. 410Arahman, N. 416Arif, S.S. 89Ariyantoro, A.R. 1Astuti, M. 48Ayu, D.F. 117